Management of Southern African Gamebirds: Opportunities and Threats - Tim Crowe (National Quail Symposium Proceedings, 2017)
Three evolutionarily quite distinct groups of galliforms contribute to a healthy wingshooting industry in southern Africa: guineafowl (Numida spp.), francolins (Scleroptila spp.) and spurfowls (Pternistis spp.). Some species, such as the helmeted guineafowl (N. meleagris), Swainson’s spurfowl (P. swainsonii) and greywing francolin (S. africanus), thrive in moderate to heavily disturbed landscapes, mainly agriculture. In fact, helmeted guineafowl and Swainson’s spurfowl increased both in abundance and range during the 20th century. Others, such as the redwing (S. levaillantii) and Orange River francolins (S. levaillantoides) are very sensitive to certain types of land use. These strikingly different responses to land use require equally diverse strategies in order to develop truly sustainable management strategies and policies. These are discussed in detail for each of these five species of gamebirds.
Keywords: management; southern African gamebirds; threat; utilization